2016
DOI: 10.1371/journal.pone.0164148
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Age and Sex on CD4+ Cell Count Trajectories following Treatment Initiation: An Analysis of the Tanzanian HIV Treatment Database

Abstract: ObjectiveNew guidelines recommend that all HIV-infected individuals initiate antiretroviral treatment (ART) immediately following diagnosis. This study describes how immune reconstitution varies by gender and age to help identify poorly reconstituting subgroups and inform targeted testing initiatives.DesignLongitudinal data from the outpatient monitoring system of the National AIDS Control Program in Tanzania.MethodsAn asymptotic nonlinear mixed effects model was fit to post-treatment CD4+ cell count trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This is consistent with observations among both HIV-infected and HIV-uninfected populations (34,43). Although this is most likely due to pathophysiological differences and differential responses to ART between males and females (44)(45)(46), the less exposure of female patients to behaviors that favorite liver disease progression such as smoking and drinking cannot be ruled out (10,(47)(48). Interestingly, we found that homosexual men or men who have sex with men (MSM) were less likely to encounter liver fibrosis progression than heterosexual men.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with observations among both HIV-infected and HIV-uninfected populations (34,43). Although this is most likely due to pathophysiological differences and differential responses to ART between males and females (44)(45)(46), the less exposure of female patients to behaviors that favorite liver disease progression such as smoking and drinking cannot be ruled out (10,(47)(48). Interestingly, we found that homosexual men or men who have sex with men (MSM) were less likely to encounter liver fibrosis progression than heterosexual men.…”
Section: Discussionsupporting
confidence: 90%
“…CD4+ T cell counts were the outcome and log-transformed due to skewness in their distributions. Because sex [41], age [42], and nadir CD4+ T cell counts [43] have been show to associate with CD4+ T cell counts and HIV disease progression, they were included as covariates. An initial regression model was fit, first controlling for each independent variable separately, and then a final model was fit adjusting for all covariates to evaluate bivariate relationships and unique relationships.…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrated that i) the CD4 count at the start of ART was the strongest predictor of CD4 count recovery, [29] ii) CD4 recovery was rapid early in the course of ART but stabilised around 12 months post ART initiation, [30] and iii) CD4 count recovery is slower in males compared to females and in older individuals compared to younger individuals. [7,8,31,32] However, the comparison of CD4 count recovery by province and calendar year is new. A number of factors may contribute to the variation in CD4 counts across provinces even after adjusting for confounding factors such as age, gender, baseline CD4 counts and viral load suppression.…”
Section: Discussionmentioning
confidence: 99%